Ultrasonic bonding method for heterogeneous microstructures using self-balancing jig1. Issue 6 (21st March 2015) - Lee, Kyoung G.; Shin, Sujeong; Kim, Byeong Il; Bae, Nam Ho; Lee, Moon-Keun; Lee, Seok Jae; Lee, Tae Jae
<x xml:space="preserve">Abstract</x> Self-balancing jig has been adapted for fabricating and bonding of heterogeneous microstructures in thermoplastic-based microfluidic device.